Sodium layered oxide, use thereof and method for producing same

By optimizing the composition and oxidation state distribution of transition metal ions, the sodium layered oxide of P2-O3 or O3 phase is formed, which solves the problem of its sensitivity to humid air and achieves better moisture resistance and electrochemical properties.

CN119790512APending Publication Date: 2025-04-08CENT NAT DE LA RECH SCI (C N R S) +2

Patent Information

Application Number
CN202380061440.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-23
Filing Date
2023-08-22
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Sodium layered oxides are sensitive to humid air, resulting in structural deterioration and degradation of battery performance, and their batch synthesis is often accompanied by sodium-rich Na3MnO4 and cubic metal oxide impurities.

Method used

A specific type of sodium layered oxide compound is used, which has an optimized transition metal ion composition and oxidation state distribution, such as NaxM1a+1-y-z-n M2b+yM3c+zM4d+nO2, and the layered structure of the P2-O3 or O3 phase is formed by adjusting the range of x, y, z, n and the oxidation number of transition metal ions, thereby improving the moisture resistance of the material.

Benefits of technology

The stability of sodium layered oxides to humid air is achieved, good electrochemical characteristics are maintained, such as circulation performance, capacity retention rate and battery cell voltage, reducing the presence of impurities and improving the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119790512A_ABST
    Figure CN119790512A_ABST
Patent Text Reader

Abstract

The invention relates to a sodium layered oxide of formula I: NaxM1a + i-y-z-n M2b + yM3c + zM4d + nO2 wherein: M1a +, M2b +, M3c + and M4d + are different transition metal ions or mixtures thereof, x is a number ranging from 0.5 to less than 1; y, z and n are numbers ranging from 0.01 to 0.85; y + z + n is less than 1; a, b, c and d are the corresponding oxidation numbers of the transition metal ions M1, M2, M3 and M4 respectively; the cumulative oxidation state a * (1-y-z-n) + (b * y) + (c * z) + (d * n) of the transition metal ions is equal to 4-x; and wherein the sodium layered oxide of formula I is not P2-Na < 2 > / 3 > Ni < 1 / 4 > Mn < 1 / 2 > Ti < 1 / 6 > Zn < 1 / 12 > O < 2 >, P2-Na < 2 > / 3 > Ni < 1 / 4 > Mn < 1 / 2 > Ti < 1 / 6 > Mg < 1 / 12 > O < 2 >, or P2-Na < 2 > / 3 > Ni < 1 / 4 > Mn < 1 / 2 > Ti < 1 / 6 > Mg < 1 / 12 > O < 2 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention generally relates to a novel sodium layered oxide compound, to a device incorporating the compound, such as an electrode comprising the sodium layered oxide compound, or in an electrochemical energy storage cell or device, such as a Na-ion battery. The present invention further relates to a method of making and / or using the compound and a device incorporating the same. Background Art

[0002] Sodium-ion batteries have been developing rapidly in recent years as they can be a cost-effective alternative to Li-ion batteries. In addition, the safety observed during external short circuit / 0V discharge of Na-ion cells makes them more attractive for large-scale applications. Different Na-ion cell chemistries are currently available, in which hard carbon is mainly used as the negative electrode and the electrolyte is based on sodium salts dissolved in organic carbonates (NaPF6 / NaClO4, etc.) as electrolyte. 1 However, the positive electrode can be made from polyanionic materials (e.g., Na3V2(PO4)2F3), layered sodium transition metal oxides (Na x MO2, x≤1 and M is one or more transition metal ions) or Prussian blue analogs (PBA). 2 Among them, the polyanion Na3V2(PO4)2F3 (NVPF) exhibits long-term structural stability and high power rate performance during cycling. 3 Each cathode family has its own advantages and disadvantages. However, sodium layered oxides are always more attractive and anticipated due to their low molecular weight, high density, and the possibility of tuning the electrochemical properties by carefully selecting transition metal ions (M). 4,5

[0003] Sodium layered oxides can crystallize in O3, P2 or P3 structures, where the letters O and P represent the octahedral / prismatic coordination of the sodium ions and the number indicates the number of MO2 layers in the unit cell. 6 For stoichiometric compounds, the O3 structure is preferred, where the Na x In MO2, x is close to 1. For non-stoichiometric compounds, the P2 / P3 structure is preferred, where Na x In MO2, x≤0.8. Among the O3, P2, and P3 phases, the O3 phase is more studied, which is attributed to its high sodium content and therefore high capacity compared to the equivalent P2 or P3 phases. However, the P2 and P3 phases are reported for their power rate performance compared to the O3 phase. Finally, a common problem in all O3, P2, and P3 phases is the continuous phase transition from the P-type phase to the O-type phase during cycling (sodium removal and re-intercalation).

[0004] Another major problem to be solved in the case of sodium layered oxides is their sensitivity to humid air. 0.67 Ni 0.33 Mn 0.67 O2 and O3 NaNi 0.5 Mn 0.5 O2 are both very sensitive to humid air. When exposed to humid air, sodium from the alkali metal layer is replaced by H + / H2O / H3O + Replacement / ion exchange to form a second phase with the formation of Na2CO3 and NaOH in the surface. + / H2O / H3O + Insertion into the structure results in poor electrochemical performance and also creates difficulties in processing electrode coatings. Due to the presence of carbonate and hydroxide impurities, the material reacting with moisture forms agglomerates which result in gelation and poor compatibility on Al foils used for electrode processing.

[0005] In the previous patent application WO 2020 / 260294, Zn and Ti co-doping in NaNi 0.5 Mn 0.5 O2 material to form O3 type Na x Ni 0.5-y Zn y Mn 0.5-z Ti z O2 (x is about 1). The phase transition of this material is similar to that of the parent O3NaNi 0.5 Mn 0.5 O2 material is reduced compared to the original material. This co-replacement method enables the full capacity of the material to be reached. Therefore, at 2.2-4.5V (vs. Na + / Na 0 ) voltage window, a capacity of 180-200 mAh / g was obtained. 0.5 Mn 0.5 Compared with O2, O3-Na x Ni 0.5-y Zn y Mn 0.5-z Ti z O2 (x is about 1) also exhibits better stability when exposed to moist air. The precursor releases Na to form Na2CO3 and / or NaOH when exposed to air for a short period of time. The improved moisture stability comes from Zn 2+ and Ti 4+ However, the exact role of these ions is still unclear.

[0006] Although this O3 phase Na x Ni 0.5-y Zny Mn 0.5-z Ti z O2 (x is about 1) materials show better stability when exposed to humid air, but there are also some problems when using them to make electrode slurries. All components such as solvents, binders, etc. need to be in completely dry (i.e., water-free) conditions. Without such conditions, the slurry leads to agglomeration and thus produces poor coatings, such as Figure 1A and Figure 1B In this case, a similar composition with less sodium was tried, hoping to improve moisture stability. However, by reducing the sodium content, Na x Ni 0.5-y Zn y Mn 0.5-z Ti z The synthesis of O2 produces a P2-O3 mixture ( Figure 2 ), always accompanied by a second phase of cubic metal oxides ((Ni a Zn b The presence of such metal oxide impurities is known to increase parasitic reactions with the electrolyte during cycling and is detrimental to battery cell performance.

[0007] EP 3 121 879 A1 discloses a P2 phase alkali metal layered oxide material comprising nickel and having the formula M x Ni a-y M 1 b M 2 c M 3 y When M 1 It is Mn, M 2 is Ti and M 3 When Zn is present, ZnO impurities are observed (see

[098] ). EP 3 121 879 A1 does not mention moisture, but discloses the following compounds: Na 2 / 3 Ni 1 / 4 Mn 1 / 2 Ti 1 / 6 Zn 1 / 12 O2、Na 2 / 3 Ni 1 / 4 Mn 1 / 2 Ti 1 / 6Mg 1 / 12 O2 and Na 2 / 3 Ni 1 / 4 Mn 1 / 2 Ti 1 / 6 Mg 1 / 12 O2.

[0008] Therefore, the growth of sodium layered oxides is hampered due to their reactivity to humid air, which leads to structural degradation and requires a moisture-free environment for storage and electrode processing. In addition, the batch synthesis of sodium layered oxides is usually associated with sodium-rich Na3MnO4 and cubic metal oxide impurities.

[0009] To overcome these difficulties, it has been unexpectedly discovered that specific types of sodium layered oxides will provide suitable moisture resistance while providing satisfactory electrochemical characteristics such as cycling performance, capacity retention (including use of full capacity) and / or battery cell voltage. Summary of the invention

[0010] The sodium layered oxide according to the present invention is a sodium layered oxide having the formula I:

[0011] Na x M1 a+ 1-y-z-n M2 b+ y M3 c+ z M4 d+ n O2, (I),

[0012] in:

[0013] M1 a+ 、M2 b+ 、M3 c+ and M4 d+ are different transition metal ions or mixtures thereof,

[0014] x is a number ranging from 0.5 to strictly less than 1 (0.5≤x<1);

[0015] y, z and n are numbers ranging from 0.01 to 0.85 (0.01≤y≤0.85, 0.01≤z≤0.85 and 0.01≤n≤0.85);

[0016] y+z+n is less than 1 (y+z+n<1);

[0017] a, b, c and d are the corresponding oxidation numbers of transition metal ions M1, M2, M3 and M4, respectively; and

[0018] The cumulative oxidation state of the transition metal ion a*(1-yzn)+(b*y)+(c*z)+(d*n) is equal to 4-x;

[0019] And wherein the sodium layered oxide having formula I is not P2-Na 2 / 3 Ni 1 / 4 Mn 1 / 2 Ti 1 / 6 Zn1 / 12 O2, P2-Na 2 / 3 Ni 1 / 4 Mn 1 / 2 Ti 1 / 6 Mg 1 / 12 O2 or P2-Na 2 / 3 Ni 1 / 4 Mn 1 / 2 Ti 1 / 6 Mg 1 / 12 O2.

[0020] Therefore, the sodium layered oxide of formula I of the present invention has a crystal structure that can be selected from the group consisting of: O3 when x ranges from 0.8 to less than 1; P2-O3 mixture when x ranges from 0.7 to 0.8, preferably between 0.701 and 0.799; P3-O3 mixture when x ranges from 0.7 to 0.85; and P2 or P3 when x≤0.7. Particularly preferably, the crystal structure of the sodium layered oxide is a P2-O3 or P3-O3 structure.

[0021] When the cumulative oxidation state is greater than 4-x, the excess sodium used in the synthesis may exist as a second phase of Na2CO3, which can be used as a sacrificial salt, as reported in Ref. 7. Alternatively, the transition metal may be stabilized at an oxidation state lower than the most stable oxidation state (e.g., Mn 3+ Instead of Mn 4+ stabilization).

[0022] Alternatively, or advantageously, another object of the invention is a sodium layered oxide having formula I':

[0023] Na x M1 a+ 1-y-z-n M2 b+ y M3 c+ z M4 d+ n O2, (I'),

[0024] in:

[0025] M1 a+ 、M2 b+ 、M3 c+ and M4 d+ are different transition metal ions or mixtures thereof,

[0026] x is a number ranging from 0.68 to strictly less than 1;

[0027] y, z, and n are numbers ranging from 0.01 to 0.85;

[0028] y+z+n is less than 1;

[0029] a, b, c and d are the corresponding oxidation numbers of metal ions M1, M2, M3 and M4, respectively; and, preferably, the cumulative oxidation state of the transition metal ions a*(1-yzn)+(b*y)+(c*z)+(d*n) is equal to 4-x. In other words, one of the objects of the present invention is a sodium layered oxide having formula I, which exhibits a layered structure of a P2-O3 or O3 phase, preferably a P2-O3 phase.

[0030] The type of layered structure P2, O3 or mixed P2-O3 or P3-O3 type can be identified by X-ray diffraction, as shown in the examples. XRD patterns can be collected using a Bruker d8 advanced diffractometer. The following parameters are set to collect X-ray pattern data:

[0031] - Detector slit = 9.5 mm

[0032] - Beam slit = 0.6 mm

[0033] - Range: 2θ = 10°-70°

[0034] - (Angstrom)(CuKα)

[0035] - Speed: 0.36 sec / step

[0036] -Increment: 0.018°

[0037] The data thus obtained are analyzed by Fullprof software, a crystallographic tool for Rietveld full spectrum fitting matching (Rietveld profiling matching) developed by Laue-Langevin Institute (Institut Laue-Langevin). XRD pattern is compared with the integrated database of the software, and is refined when necessary. Phases are defined by digital x, and if necessary, defined by using X-ray diffraction (including but not limited to the above-described device). Advantageously, the compound of the present invention is a layered metal oxide with a structure that is P2, O3, P2-O3 or P3-O3 phase, which means that the compound is composed of at least 95%, preferably 99% phase P2, phase O3, phase P2-O3 or phase P3-O3.

[0038] Without being bound by this statement, it appears that the stability of the sodium layered oxides of the present invention to reactions with moisture is related to their redox potential. Materials with low potential redox reactions can undergo oxidation in contact with H2O and O2 in the atmosphere. O3 sodium layered oxides generally exhibit low potential redox reactions (less than 2.4 V relative to Na + / Na 0), so it is sensitive to humid air. First, by introducing Ti into the structure 4+ To establish the improvement of moisture stability, the introduction of Ti 4+ By increasing the ionicity of MO bonds, Ni 2+ The redox potential of O3NaNi 0.5-y Zn y Mn 0.5-z Ti z O2 material shows better performance than O3 NaNi 0.5 Mn 0.5 O2 has better stability to humid air. However, when moving to the P2 phase and P2-O3 phase reported in this application, for Ni 2+ / Ni (2+n)+ Redox, observed at about 3V (vs. Na + / Na 0 ) This high redox potential helps improve the material's stability to humid air.

[0039] In addition to high redox potentials, the P2-O3 materials also exhibit differences in the particle surface, where surface enrichment of transition metal ions is observed by high-resolution transmission electron microscopy (HAADF-STEM).

[0040] According to the present invention, M1 a+ 、M2 b+ 、M3 c+ and / or M4 d+ Advantageously selected from the group consisting of: Period 4 transition metals, namely: scandium (Sc), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), and zinc (Zn). Period 5 transition metals, namely yttrium (Y), zirconium (Zr), niobium (Nb), molybdenum (Mo), technetium (Tc), ruthenium (Ru), rhodium (Rh), palladium (Pd), silver (Ag), and cadmium (Cd) are also contemplated, although very expensive. Period 6 and 7 transition metals and in particular tungsten (W), iridium (Ir), platinum (Pt) and gold (Au) are also contemplated to fall within the definition of the claimed invention.

[0041] Advantageously, transition metal ions (M1, M2, M3 and M4) are selected that are in their most stable oxidation state at room temperature. This has been shown to be particularly helpful in synthesizing the final material under slow / furnace cooling without the need for quenching. It is also particularly helpful in avoiding cubic metal oxide impurities.

[0042] Preferably, in formula I or I', M1 is Ni. Further preferably, in formula I or I', M2, M3 and M4 are selected from the group consisting of: Mg, Zn, Cu, Fe, V, Cr, Mn, Ge, Sn, Ti, Zr and Co and mixtures thereof, preferably from the group consisting of: Zn, Mn, Ti, Cu, Fe, Mg and mixtures thereof, even more preferably from the group consisting of: Zn, Mn and Ti.

[0043] It is further preferred that, in formula I or I', x is selected within the range of 0.6 to 0.9.

[0044] Advantageously, in the sodium layered oxide having formula I or I', M1 is Ni 2+ , M2 and M4 are Mn 4+ or Ti 4+ , and y is less than 0.07, preferably less than 0.06 and advantageously less than 0.05.

[0045] In particular, the compounds of the present invention as described above may have the formula Na x Ni 1-y-z-n M2 2+ y Mn z Ti n O2(II), wherein M2 is selected from the group consisting of: Mg, Zn, Cu, Fe, V, Cr, Ge, Sn, Zr, Co and mixtures thereof, and is advantageously selected from the group consisting of: Mg, Zn, Cu, Fe and mixtures thereof. M2 is preferably Zn.

[0046] Advantageously, the value y of the sodium layered oxide of formula II is less than 0.07, preferably less than 0.06 and advantageously less than 0.05.

[0047] Compounds of formula II are particularly advantageous, which correspond to sodium layered oxides in which M1, M2, M3 and M4 are Ni, Zn, Mn and Ti, respectively, and which therefore have the formula Na x Ni 1-y-z-n Zn y Mn z Ti n O2(III). Compounds of formula (III) are particularly preferred, which contain Ni 2+ 、Zn 2+ , Mn 4+ and Ti 4+ ions. Use cheaper elements such as Mn, Ti and Zn and only minimal Ni 2+ions help reduce the overall cost of the material. The layered metal oxides exhibited a capacity of 120 mAh / g with an average voltage of 3.7 V (a very high average voltage compared to reported P2 phases) and showed long-term cycling stability.

[0048] The specific compound of the present invention is Na 0.67 Ni 0.3 Zn 0.03 Mn 0.52 Ti 0.15 O2.

[0049] Another specific compound of the present invention is Na 0.76 Ni 0.35 Zn 0.03 Mn 0.52 Ti 0.1 O2.

[0050] Another specific compound of the present invention is Na 0.85 Ni 0.38 Zn 0.04 Mn 0.48 Ti 0.1 O2.

[0051] In a particularly advantageous embodiment of the present invention, the sodium layered oxide having formula (III) is selected from the group consisting of: P2-Na 0.67 Ni 0.3 Zn 0.03 Mn 0.52 Ti 0.15 O2, P2-O3-Na 0.76 Ni 0.35 Zn 0.03 Mn 0.52 Ti 0.1 O2 and P3-O3-Na 0.85 Ni 0.38 Zn 0.04 Mn 0.48 Ti 0.1 O2.

[0052] Alternatively, ions such as Fe 2+ , Cu 2+ or Mg 2+ Can be advantageously used as Zn 2+ full or partial replacement of .

[0053] Therefore, particularly preferred compounds or materials having formula II are those having formula Na x Ni 1-y-z-n Fe y Mn z Ti n O2(IV) compounds or materials.

[0054] The preferred compound of the present invention is Na 0.7 Ni 0.2 Fe 0.3 Mn 0.35 Ti 0.15 O2.

[0055] The preferred compound of the present invention is Na 0.7 Ni 0.25 Fe 0.2 Mn 0.40 Ti 0.15 O2.

[0056] Also particularly preferred are additional compounds or materials of formula II having the formula Na x Ni 1-y-z-n Cu y Mn z Ti n O2(V) or Na x Ni 1-y-z-n Mg y Mn z Ti n O2(VI).

[0057] A particularly preferred compound of the present invention is Na 0.67 Ni 0.3 Cu 0.03 Mn 0.52 Ti 0.15 O2.

[0058] A particularly preferred compound of the present invention is Na 0.67 Ni 0.3 Mg 0.03 Mn 0.52 Ti 0.15 O2.

[0059] Another aspect of the present invention relates to a method for preparing a sodium layered oxide as defined above, i.e. a method for preparing a sodium layered oxide having formula I:

[0060] Na x M1 a+ 1-y-z-n M2 b+ y M3 c+ z M4 d+ n O2, (I),

[0061] in:

[0062] M1 a+ 、M2 b+、M3 c+ and M4 d+ are different transition metal ions or mixtures thereof,

[0063] x is a number ranging from 0.5 to strictly less than 1;

[0064] y, z, and n are numbers ranging from 0.01 to 0.85;

[0065] y+z+n is less than 1;

[0066] a, b, c and d are the corresponding oxidation numbers of metal ions M1, M2, M3 and M4, respectively; and

[0067] The cumulative oxidation state of the transition metal ion a*(1-yzn)+(b*y)+(c*z)+(d*n) equals 4-x.

[0068] According to the present invention, the method comprises the following steps:

[0069] (a) mixing a powder of a sodium precursor and a powder of a transition metal precursor of the sodium layered oxide in stoichiometric amounts to obtain a solid powdery mixture;

[0070] (b) heating the solid powdery mixture at a temperature ranging from 500° C. to 900° C., preferably in an air atmosphere, to obtain a calcined powder;

[0071] (c) cooling the calcined powder at a rate of 1.5° C. / min (preferably 1° C. / min) or less;

[0072] (d) grinding the calcined powder to obtain a ground calcined powder;

[0073] (e) heating the solid powdery mixture at a temperature ranging from 700° C. to 1100° C., preferably in an air atmosphere, to obtain a ground re-calcined powder;

[0074] (f) cooling the ground re-calcined powder, advantageously at a rate of 1.5° C. / min (preferably 1° C. / min) or less.

[0075] Precursors may be selected from suitable compounds including salts and oxides of sodium or the selected metal. Non-limiting but preferred precursors are Na2CO3, NiO, ZnO, CuO, MgO, Fe2O3, Mn2O3 and TiO2. It has been found that, especially if Mn is used, it is desirable to avoid using excess Na2CO3 in order to reduce impurities such as Na2CO3 / Na3MnO4. Therefore, when selecting the amount of precursor to be used, it is preferred to strictly adhere to the stoichiometry of the compound to be obtained.

[0076] "Strictly adhere to the stoichiometry" means that the amount of the precursor should advantageously be chosen to be ±5%, preferably ±1%, even more preferably ±0.5% of the stoichiometric amount.

[0077] The precursor is preferably milled or ground, for example using a ball mill. In this case, the ratio of balls to powder may be in the range of 1:10 to 1:30, preferably about 1:20. The mixture is then heated at a temperature that is advantageously 800°C or lower, for example 750°C to 799°C. This is the first annealing or calcining step. This first calcining step may be carried out for a period ranging from 1 h to 24 h, preferably a period ranging from 4 h to 7.5 h, and more preferably a period ranging from 5 h to 6 h, such as 6 h. This step may be carried out at atmospheric pressure.

[0078] The intermediate grinding step d) can be carried out by ball milling under the same conditions as described above. This grinding step can be carried out for a time ranging from 10 minutes to 2 hours; a grinding step of 1 hour was found to be effective.

[0079] Advantageously, the second or calcination step e) may be carried out at a temperature which may be selected from 900°C to 1000°C, or alternatively may be in the range of 900°C to 999°C or 900°C to 949°C.

[0080] This method was found to produce a homogeneous material having the desired single phase or combined P2, O3, P2-O3 or P3-O3 phases. This second calcination step may be carried out for a period ranging from 1 h to 24 h, preferably for a period ranging from 4 h to 7.5 h, and more preferably for a period ranging from 5 h to 6 h, such as 6 h. This step may be carried out at atmospheric pressure.

[0081] Both the first calcination step and the second calcination step may be performed at a heating rate ranging from 1° C. / min to 10° C. / min, and preferably 3° C. / min.

[0082] It is also advantageous that when either or both of cooling steps c) and / or f) are performed, cooling is performed at a predetermined rate of 1°C / min or less. This rate is important for obtaining optimal results, especially the formation of the P3-O3 phase (see Example 8).

[0083] Alternatively, the materials of the present invention may also be synthesized using solution synthesis such as coprecipitation-assisted solid-state synthesis, sol-gel, hydrothermal, combustion synthesis, etc. In solution synthesis, the precursors used are typically salts such as metal nitrates, sulfates, carbonates, etc. The same precursors as described above (i.e., oxides) may also be used, but then they need to be dissolved (e.g., in nitric acid).

[0084] Another object of the present invention is a compound (ie a sodium layered oxide) obtained or obtainable according to the process of the present invention.

[0085] Another object of the present invention is an electrode material comprising:

[0086] - sodium layered oxides according to the invention and described above;

[0087] - conductive additives, such as carbon black; and

[0088] -Optionally a polymeric binder.

[0089] The polymer binder may be, for example, PVDF (polyvinylidene fluoride), CMC (sodium carboxymethylcellulose) and derivatives thereof, with PVDF being preferred.

[0090] The relative proportions of the components can be selected within the ranges indicated below:

[0091] - 4 wt.% to 20 wt.%, preferably 4 wt.% to 15 wt.% of conductive additives, such as conductive carbon (carbon black, super P carbon from TIMCAL);

[0092] - 3 wt.% to 6 wt.% of a polymer binder, such as PVDF; and

[0093] - 20 wt.% - 40 wt.% of a solvent (or dispersant), such as N-methylpyrrolidone (NMP).

[0094] A method for making the electrode material mentioned above is another object of the present invention. The method comprises mixing the sodium layered oxide according to the present invention with a conductive additive and a final polymer binder. The conductive additive is added in a suitable proportion, such as 5wt.% to 20wt.% relative to the mass of the sodium layered oxide.

[0095] When a binder is used, the mixture is dispersed in a solvent (ie, a dispersant) to obtain a slurry, particularly a uniform slurry.

[0096] Another object of the present invention is a positive electrode comprising an electrode material of the present invention in working contact with a current collector. Preferably, the current collector comprises a carbon material or a metal such as aluminum. Further preferably, a layer of the sodium layered oxide or electrode material of the present invention is cast on the current collector, which may be in the shape of a sheet such as aluminum foil.

[0097] A method for making the above-mentioned positive electrode is another object of the present invention. The method comprises associating or attaching the compound or electrode material of the present invention to a current collector. Pressure can be simply applied. When a binder / dispersant is used, the obtained slurry can be cast onto a current collector such as aluminum foil. The dispersant is then removed, for example, by heating (e.g., 120° C.).

[0098] Advantageously, a compression or pressing step may be applied, which may be performed by means of a roller machine, to produce or improve associations between the compounds of the invention or the electrode materials.

[0099] Another object of the invention is an electrochemical cell comprising:

[0100] - electrolytes;

[0101] - a negative electrode configured to reversibly accept sodium ions from an electrolyte and reversibly release sodium ions into the electrolyte, the negative electrode having at least one current collector;

[0102] a positive electrode comprising a compound as described above (i.e., a sodium layered oxide) or an electrode material configured to reversibly accept sodium ions from an electrolyte and reversibly release sodium ions into the electrolyte, the positive electrode having at least one current collector; and

[0103] - A separator admixed with an electrolyte comprising sodium ions, which is in contact with both the negative electrode and the positive electrode.

[0104] The separator is typically selected from the group consisting of glass fibers, polyolefin separators and cellulose-based films. In particular, the membrane may be a polypropylene (PP) film, a polyethylene (PE) film or advantageously a multilayer film of PP+PE+PP.

[0105] The negative electrode comprises a negative electrode or anode electrode material, which is advantageously sodium metal, a carbonaceous compound, hard carbon, antimony, tin, phosphorus or a mixture thereof, such as a mixture of Sn and hard carbon. The anode material typically comprises a conductive additive, such as carbon black; and optionally a polymer binder. The additives and binders and their relative proportions may be as described for the positive electrode material. The negative electrode may also have the same structure and a similar current collector as the positive electrode. In addition, the manufacturing method may be the same as described above.

[0106] The electrolyte of the electrochemical cell of the present invention may comprise:

[0107] - sodium salts, such as sodium hexafluorophosphate (NaPF6), sodium perchlorate (NaClO4), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium bis(pentafluoroethanesulfonyl)imide (NaBETI), sodium tetrafluoroborate (NaBF4), Na[B(hfip)4]·DME (hfip=hexafluoroisopropoxy, OiPrF) and Na[B(pp)2] (pp=perfluoropinacol, O2C2(CF3)4) or mixtures thereof;

[0108] - solvents (or dispersants), such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), propylene carbonate (PC), ethylene carbonate (EC); esters, such as methyl acetate (MA), ethyl acetate (EA), ethyl propionate (EP), or methyl propionate (MP), or mixtures thereof, such as EC / EP mixtures; and

[0109] - Optionally, additives such as vinylene carbonate (VC), 1,3-propane sultone (PS), succinonitrile (SN), sodium difluoro(oxalato)borate (NaODFB) or mixtures thereof, such as VC and SN.

[0110] The sodium salt NaPF6 is preferred.

[0111] The concentration of the sodium salt may be in the range of 0.1 mol / L to 3 mol / L, preferably 0.5 mol / L to 2 mol / L, relative to the total volume of the one or more solvents.

[0112] The concentration of the electrolyte additive can generally vary from 0.05 wt.% to 10 wt.% relative to the total weight of the electrolyte composition. Advantageously, the following concentrations of specific additives are used:

[0113] - 0.1 wt.% to 10 wt.%, preferably 0.5 wt.% to 5.0 wt.% of vinylene carbonate (VC),

[0114] - 0.1 wt.% to 5 wt.%, preferably 0.5 wt.% to 2.0 wt.% of succinonitrile (SN),

[0115] - 0.05 to 10 wt.%, preferably 0.2 to 1.0 wt.% of sodium difluoro(oxalato)borate (NaODFB).

[0116] The electrolyte can be prepared by: if a mixture of solvents is considered (e.g. a mixture of EC / PC / DMC in a 1:1:2 volume ratio), the solvents are mixed; then a sodium salt (e.g. NaPF6 at a concentration of 1 mol / L) is added; an additive (e.g. 5.0 wt.% VC, 1.0 wt.% SN) is added to the solution. Preferably, these steps are carried out under stirring and the order of the addition steps can be changed, such as first adding the additive to the solvent and then adding the salt. The entire method is advantageously carried out in an inert atmosphere (e.g. under Ar or N2).

[0117] Another object of the present invention is a battery comprising a series of electrochemical cells of the present invention. The positive electrode, separator and negative electrode can be stacked layer by layer (one electrode, one separator), and finally folded and / or wound onto the cell core. The cell core is placed in a cell shell and dried. Drying can be carried out at 85° C. under vacuum (e.g., less than -1.0 bar) for 24 hours. Then, the electrolyte is injected and sealed into the Na-ion battery of the present invention. The method for manufacturing the battery of the present invention is another object of the present invention.

[0118] Electrochemical cells or batteries according to the present invention may be in various suitable configurations, such as button cells, pouch cells, cylindrical cells (18650, 21700, 36500, etc.), or prismatic cells.

[0119] Yet another object of the present invention is the use of the compounds or materials according to the invention as electroactive compounds or materials in a battery cell or battery, preferably as positive electrode material.

[0120] The use of the battery according to the present invention includes, for example, combining it in a microgrid stabilization grid, an electrochemical storage device for intermittent renewable energy (e.g., solar energy, wind energy), a mobile storage device for electric vehicles (scrapped rechargeable buses, rental fleets), a home power storage device, an emergency power supply or energy storage device for hospitals, schools, factories, computer clusters, servers, companies, and any other public and / or private buildings or infrastructure. The compound according to the present invention or the device combining the compound can be used in industries such as the following fields: automotive, computer, banking, video games, leisure, creativity, culture, cosmetics, life sciences, aviation, pharmacy, metal and steel, railways, military, nuclear, ships, aerospace, food, agriculture, construction, glass, cement, textiles, packaging, electronics, petrochemicals, and chemical industries.

[0121] The foregoing and other objects, aspects, features and advantages of the present invention will become more apparent from the following embodiments and claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0122] The present invention will now be described with reference to the following drawings, in which:

[0123] Figure 1A The slurry of the comparative example is shown, and Figure 1B This slurry is shown applied as a coating onto an aluminum foil.

[0124] Figure 2 The Na content of Na with varying amounts from 1 to 0.7 is shown. x Ni 0.45 Zn 0.05 Mn 0.4 Ti 0.1 X-ray diffraction (XRD) pattern of O2.

[0125] Figure 3 The three different sodium layered oxides prepared according to the present invention and described in Example 2 are shown in Figure 2 and the prior art compound O3-phase NaNi 0.45 Zn 0.05 Mn 0.4 Ti 0.1 X-ray diffraction patterns of O2 comparison.

[0126] Figure 4 shows the as-prepared ( Figure 4A ) and after exposure to 55% relative humidity ( Figure 4B )of Figure 3 X-ray diffraction pattern of the compound.

[0127] Figure 5 A slurry comprising the P2-O3-phase Na2O3 according to the invention is shown as a coating applied to an aluminum foil. 0.76 Ni 0.35 Zn 0.03 Mn 0.52 Ti 0.1 O2.

[0128] Figure 6 P2 Na 0.67 Ni 0.3 Zn 0.03 Mn 0.52 Ti 0.15 O2(P2 Na 0.67 MO2)、P2-O3Na 0.76 Ni 0.35 Zn 0.03 Mn 0.52 Ti 0.1 O2(PO-Na 0.76 MO2), O3 Na 0.9 Ni 0.4 Zn 0.05 Mn 0.4 Ti 0.15 O2(O3 Na0.9 MO2) and prior art O3 NaNi 0.45 Zn 0.05 Mn 0.4 Ti 0.1 Cycling performance of O2(O3NaMO2) in a Na-ion half-cell with sodium metal as the anode.

[0129] Figure 7 Shown with Figure 6 Cycling performance of the same compounds after exposure to 55% relative humidity.

[0130] Figure 8 shows the Figure 6 Electrochemical properties of the same compounds in a Na-ion full cell with hard carbon as negative electrode, where Fig. 8A shows the characteristic curve of capacity versus composition, Figure 8B The capacity retention ratio is shown, and Figure 8C A histogram showing the energy obtained and points representing the average cell voltage for these materials (right axis) is shown.

[0131] Fig.9A P2 Na 0.7 Ni 0.2 Fe 0.3 Mn 0.35 Ti 0.15 X-ray diffraction pattern of O2.

[0132] Fig. 9B P2 Na 0.7 Ni 0.2 Fe 0.3 Mn 0.35 Ti 0.15 Cycling performance of O2 in a Na-ion half-cell with Na metal as the anode.

[0133] Fig. 10A P2 Na 0.7 Ni 0.25 Fe 0.2 Mn 0.35 Ti 0.15 X-ray diffraction pattern of O2.

[0134] Fig. 10B P2 Na 0.7 Ni 0.25 Fe 0.2 Mn 0.35 Ti 0.15 Cycling performance of O2 in a Na-ion half-cell with Na metal as the anode.

[0135] Fig.11The following (from top to bottom) cycling performances in a Na-ion half-cell with sodium metal as the negative electrode are shown: P2 Na 0.67 Ni 0.3 Cu 0.03 Mn 0.52 Ti 0.15 O2、Na 0.67 Ni 0.3 Mg 0.03 Mn 0.52 Ti 0.15 O2 and P2Na 0.67 Ni 0.3 Zn 0.03 Mn 0.52 Ti 0.15 O2.

[0136] Fig.12 The P2-O3-Na of Example 6 is shown 0.76 Ni 0.35 Zn 0.03 Mn 0.52 Ti 0.1 XRD pattern of O2, where the synthesis was carried out with excess Na2CO3. The XRD pattern shows Na2CO3 as a second phase (marked with an asterisk in the figure).

[0137] Fig.13 shows that by repeated reheating Fig.12 The mixture obtained in the reaction mixture forms O3-Na 0.76 Ni 0.35 Zn 0.03 Mn 0.52 Ti 0.1 O2.

[0138] Fig.14 The following charge first derivative curves are shown: (a) O3-NaNi 0.5 Mn 0.5 O2, which corresponds to WO 2020 / 260294, (b) Ti-substituted O3-NaNi 0.45 Zn 0.05 Mn 0.4 Ti 0.1 O2, which corresponds to Comparative Example 1, and (c) P2-Na 0.67 Ni 0.3 Zn 0.03 Mn 0.52 Ti 0.15 O2, which is according to the invention and obtained in Example 2.

[0139] Fig.15 (a) and Fig.15 (b) shows the P2-O3-Na0.76 Ni 0.35 Zn 0.03 Mn 0.52 Ti 0.1 High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) image of O2. Fig.15 (c) shows the Fig.15 HAADF signal distribution curve of the area marked in (b).

[0140] Fig.16 The Na of Example 7 is shown 0.85 Ni 0.38 Zn 0.04 Mn 0.48 Ti 0.1 XRD pattern of O2. Fig.17 The P3-O3-Na of Example 7 is shown 0.85 Ni 0.38 Zn 0.04 Mn 0.48 Ti 0.1 High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) image of O2.

[0141] Fig.18 The as prepared ( Fig.18 (a)) and after exposure to 55% relative humidity for 48 h ( Fig.18 (b)) XRD pattern of the compound of Example 7.

[0142] Fig.19 O3-Na 0.85 Ni 0.38 Zn 0.04 Mn 0.48 Ti 0.1 High temperature XRD analysis of O2.

[0143] Fig. 20 The Na of Example 8 is shown 0.85 Ni 0.38 Zn 0.04 Mn 0.48 Ti 0.1 XRD pattern of O2( Fig. 20 (a)) and Na of Example 7 0.85 Ni 0.38 Zn 0.04 Mn 0.48 Ti 0.1 XRD pattern of O2( Fig. 20 (b)) comparison.

[0144] Comparative Example 1

[0145] O3-phase NaNi0.45 Zn 0.05 Mn 0.4 Ti 0.1 O2 was obtained by solid state synthesis as described in Example 1b of WO 2020 / 260294. A slurry of this material was obtained by mixing it with:

[0146] - 15 wt.% conductive carbon (carbon black, super P carbon from Temeco),

[0147] -5wt.% PVDF as binder;

[0148] - 30 wt.% N-methylpyrrolidine (NMP) as solvent. The solvent (ie dispersant) will be removed later during drying and its amount can therefore be selected to obtain the desired slurry viscosity.

[0149] Then, the transition metal composition was kept constant and the sodium stoichiometry was varied: Na 0.9 Ni 0.45 Zn 0.05 Mn 0.4 Ti 0.1 O2、Na 0.8 Ni 0.45 Zn 0.05 Mn 0.4 Ti 0.1 O2 and Na 0.7 Ni 0.45 Zn 0.05 Mn 0.4 Ti 0.1 O2 powder is used with O3-phase NaNi 0.45 Zn 0.05 Mn 0.4 Ti 0.1 O2 is obtained in the same way.

[0150] Figure 1A It shows that in O3 NaNi 0.45 Zn 0.05 Mn 0.4 Ti 0.1 To form the electrode, the slurry was coated on aluminum foil (see Figure 1B ). The coating became non-uniform due to agglomerates in the slurry. The cause of the agglomerate formation was found to be the undried PVDF-NMP mixture containing a few ppm (about 10 ppm) of water.

[0151] Na with sodium content x of 1, 0.9, 0.8 and 0.7 x Ni 0.45 Zn 0.05 Mn 0.4 Ti0.1 The X-ray diffraction pattern of the O2 component is shown in Figure 2 By reducing the sodium content to 0.7, the P2 phase starts to appear. However, in all these materials, cubic metal oxide impurities (*cubic MO) are observed, whose content increases with decreasing sodium content. This shows the importance of fine-tuning the transition metal stoichiometry according to the sodium stoichiometry.

[0152] Example 2

[0153] The following sodium layered oxides were prepared:

[0154] P2-phase Na 0.67 Ni 0.3 Zn 0.03 Mn 0.52 Ti 0.15 O2

[0155] P2-O3-phase Na 0.76 Ni 0.35 Zn 0.03 Mn 0.52 Ti 0.1 O2

[0156] O3-Phase Na 0.9 Ni 0.4 Zn 0.05 Mn 0.4 Ti 0.15 O2

[0157] These materials were synthesized in 100 g batches. Stoichiometric amounts of sodium and transition metal precursors (Na2CO3, NiO, ZnO, CuO, MgO, Fe2O3, Mn2O3 and TiO2) were mixed together by hand grinding followed by dry ball milling for one hour. The ball milling step was performed using a SPEX 8000MTM mixer mill using ball milling balls and containers made of hardened steel. The ratio of balls to powder was about 1:20. The mixture was transferred to an alumina crucible and heated at 3°C ​​min in an air atmosphere. -1 The calcined powder was heated to 800°C for 6 h at a heating rate of 1°C / min, followed by slow cooling (1°C / min) to room temperature, followed by intermediate ball milling for one hour to ensure homogeneity and further heating at 900°C / 1000°C for 6 hours under the same conditions as above. Excess Na2CO3 was strictly avoided to eliminate Na2CO3 / Na3MnO4 impurities. The calcined powder was slowly cooled (1°C / min) and immediately transferred to an argon-filled glove box to avoid any reaction with moisture / air. Alternatively, the material can also be synthesized using solution synthesis such as co-precipitation-assisted solid-state synthesis, sol-gel, hydrothermal, combustion synthesis, etc. As Figure 3As shown, the material with the lowest sodium content (x=0.67) crystallizes in the P2 phase, and slightly higher sodium amounts produce a P2-O3 mixture (x=0.76). In the case of x=1 and 0.9, a pure O3 phase is obtained. However, the material with x=1 (prior art) exhibits cubic metal oxide impurity peaks, which are reduced for the x=0.9 phase.

[0158] When the sodium content is equal to or less than 0.67 (x≤0.67), a strictly pure P2 phase is formed. Similarly, for a sodium content of 0.8-1, more specifically for x=1, an O3 phase is formed. A P2-O3 mixture can be considered to be 75% of the P2 phase (x=0.67) and 25% of the O3 phase (x=1).

[0159] Compound P2-phase Na of the present invention 0.67 Ni 0.3 Zn 0.03 Mn 0.52 Ti 0.15 O2, P2-O3-phase Na 0.76 Ni 0.35 Zn 0.03 Mn 0.52 Ti 0.1 O2 and O3-phase Na 0.9 Ni 0.4 Zn 0.05 Mn 0.4 Ti 0.15 O2 and prior art compounds O3-phase NaNi 0.45 Zn 0.05 Mn 0.4 Ti 0.1 The moisture sensitivity of O2 was tested by storing them at a controlled relative humidity (RH) of 55%. A saturated solution of Mg(NO3)2.6H2O (Sigma Aldrich) in water was used to control the relative humidity. The saturated magnesium nitrate solution and the samples under analysis were kept in a sealed desiccator to ensure the required relative humidity.

[0160] As shown in Figure 4, no or negligible degradation was observed for the P2 and P2-O3 compositions, and for the O3-phase Na 0.9 Ni 0.4 Zn 0.05 Mn 0.4 Ti 0.15 Little degradation was observed for O2, while for O3-phase NaNi 0.45 Zn 0.05 Mn 0.4 Ti 0.1More degradation was observed with O2. This phenomenon was again confirmed when the “as prepared” and “air exposed” materials were cycled in Na metal half-cells ( Figure 7 ).

[0161] P2-O3-phase Na 0.76 Ni 0.35 Zn 0.03 Mn 0.52 Ti 0.1 The slurry of O2 was prepared as described in Comparative Example 1. The slurry for electrode coating was made outside the drying chamber in a humid air atmosphere and, as Figure 5 As shown, no gelling or agglomeration was observed.

[0162] Example 3: Cycling Performance and Other Characteristics

[0163] The prepared sodium layered oxides were used due to their electrochemical properties and tested in half cell and full cell configurations.The electrodes according to the invention were manufactured by selecting one or more of the layered oxide compounds obtained in Example 2.

[0164] The layered oxide active materials (positive or working electrode) in all battery cell configurations were used in powder form. The layered oxide materials for electrochemical analysis were mixed with 15w / w% carbon black (super P carbon, 25 Temeco) and ball milled for 30min using a SPEX 8000M mixer mill. 3g of oxide was ground using a hardened steel ball mill container with balls made of hardened steel, where the weight ratio of compound to ball was 1:35. The cycling performance of the material was tested in a Swagelok half-cell using Na metal as the counter electrode and in a button-type Na-ion full-cell using a hard carbon negative electrode.

[0165] The active material sodium layered oxide for electrochemical analysis was mixed with 15% carbon to improve electronic conductivity, and the powder electrode was used as is for all electrochemical analyses.

[0166] The hard carbon counter electrode used in the full cell assembly was prepared in ambient atmosphere outside the glove box. The hard carbon negative electrode powder was provided by Aekyung Petrochemical, South Korea. The average particle size and BET surface area of ​​this hard carbon were 9 μm and 3.29 m 2 g -1The hard carbon powder thus obtained was mixed with 4 w / w% conductive carbon (super P carbon from Temeco) and a binder. The binder used here was PVDF in N-methylpyrrolidine (NMP) or sodium carboxymethyl cellulose 25 and / or its derivatives in an aqueous solvent. A negative electrode slurry was prepared by mixing the active material, conductive carbon and binder in NMP in a ratio of 92:4:4, respectively. The slurry thus obtained was mixed with 5-6 mg·cm -2 The mass loading of 200 μm was coated on Al foil. The coated hard carbon film was calendered to reduce the porosity of the electrode to nearly 50%. The electrode was cut into 8-13 mm diameter discs and dried at 80 °C before use in full cell assembly and stored in an argon-filled glove box.

[0167] The positive and negative active materials are balanced according to their practically achievable capacities. For example, the hard carbon electrodes used in all battery cell assemblies exhibit 300 mAh g -1 In this case, when the positive electrode shows about 170 mAh g -1 When the positive electrode is used, a positive material to negative material weight ratio of (O3NaMO2) / (hard carbon) of about 1.7:1 is used in order to balance the capacity of the positive electrode. However, the hard carbon negative electrode is used in excess of about 4w / w% to avoid any sodium plating. In other words, an additional amount of negative electrode active material in terms of Mg is used to obtain an additional capacity of 4% of the actual amount of negative hard carbon required to balance the positive electrode. In other words, once the electrode capacity is known, the amount of active material on either electrode is adjusted so that the capacity ratio of each electrode is expressed as follows:

[0168] Capacity ratio = positive battery cell capacity / negative battery cell capacity = pc / ne

[0169] Then, the total mass of active compound for each electrode was adjusted so that the negative electrode mass of active compound was as follows:

[0170] Negative electrode mass = positive electrode mass × (pc / ne), where pc is lower than ne.

[0171] The full cell was a 2032 (diameter = 20 mm, height = 3.2 mm) button cell. The hard carbon coated on the aluminum foil electrode described above was used as the negative electrode, with 0.8-1 ml of 1 M NaPF6 in propylene carbonate (PC) as the electrolyte and two layers of glass fiber separator 7' (Whatmann, model GF / D (pore size: 2.7 μm, diameter: 5.5 cm, thickness: 675 μm)). The separator 7' was cut into discs with a diameter of about 18 mm.

[0172] In our experiments, the P2 material Na 0.67Ni 0.3 Zn 0.03 Mn 0.52 Ti 0.15 O2( Figure 3 ) exhibited high stability when exposed to humid air ( FIG4 ), but had the smallest capacity of about 125 mAh / g among the compositions studied ( Figure 5 ).

[0173] like Figure 6 As shown, by increasing the sodium content to >0.7, the material crystallizes in a predominantly P2 phase with a small amount of O3 phase. By doing so, the practical capacity increases to about 140 mAh / g, and the material is found to be very stable when exposed to humid air (Figures 4 and Figure 7 This stability when exposed to humid air is due to the high P2 phase content and the presence of Zn 2+ and Ti 4+ ions in the O3 phase. Therefore, by treating the slurry in normal air / atmosphere, the material can be coated into a smooth and uniform electrode film ( Figure 5 ). Further increasing the sodium content, the material crystallizes into a pure O3 phase, which however has a better stability to humid air (eg, x = 0.9).

[0174] Figure 7 It shows that the P2 phase is exposed ( Figure 7 ) exhibited exactly the same electrochemical performance before and after exposure to humid air, indicating its stability to humid air. However, the phase containing O3 components showed relatively poor electrochemical performance after exposure to humid air. The overall stability to humid air follows the order 0.67Na>>0.76Na>0.9Na>1Na.

[0175] Figure 8 compares the electrochemical performance of four different compositions in a Na-ion full battery cell. Fig. 8A The cycling characteristic curves in show that the maximum capacity obtained is the smallest for the P2 phase and the largest for the O3 phase. The capacities above 3V are very close for all compositions, indicating that if the application requires cycling only above 3V, all 4 phases studied will have similar capacities regardless of the total capacity. However, the P2-O3 intergrowth is good for the zero-volt stability of the battery cell during an external short circuit because it exhibits a low voltage redox compared to pure P2-type materials. Figure 8B The capacity retention was compared, where all four samples achieved similar capacity retention. Figure 8C The specific energy and average voltage of the battery cells were compared, with the P2 phase exhibiting the largest average voltage.

[0176] Next, the P2 and O3 phase materials were analyzed for possible transition metal dissolution during cycling. In order to obtain a desodiumized electrode, the sodium layered oxide was charged to 4.5V (100% SOC) and washed with dimethyl carbonate (DMC). The recovered electrodes were treated with 1M NaPF6 in an organic carbonate and stored at 55°C for 1-3 weeks. The dissolved Ni content of the electrolyte recovered from the solid by filtration was analyzed by inductively coupled plasma (ICP) analysis. Dissolved transition metal ions not only degrade the electrochemical properties of the positive electrode, but may also poison the negative electrode (HC in a Na-ion battery cell). Compared to the O3 phase, the phase with a large P2 content shows less Ni dissolution in the electrolyte (0.202% Ni for P2, compared to 2% Ni for O3).

[0177] As already disclosed above, it appears that the stability of sodium layered oxides to reactions with moisture is related to their redox potential. O3 sodium layered oxides generally exhibit low potential redox reactions (less than 2.4 V, relative to Na + / Na 0 ,like Fig.14 (a)), and is therefore sensitive to humid air. First, by introducing Ti 4+ To establish the improvement of moisture stability, the introduction of Ti 4+ By increasing the ionicity of MO bonds, Ni 2+ The redox potential (no redox reaction was observed below 2.5 V, Fig.14 (b)). However, although the obtained O3-NaNi 0.45 Zn 0.05 Mn 0.4 Ti 0.1 O2 material shows better performance than O3-NaNi 0.5 Mn 0.5 O2 has better stability to humid air. But when it moves to the P2 phase (here, with P2-Na 0.67 Ni 0.3 Zn 0.03 Mn 0.52 Ti 0.15 O2), for Ni 2+ / Ni (2+n)+ Redox, observed at 2.85V (vs. Na + / Na 0 ,like Fig.14 This high redox potential helps improve the material's stability to humid air.

[0178] In addition to the high redox potential, the P2-O3-Na 0.76 Ni0.35 Zn 0.03 Mn 0.52 Ti 0.1 O2 (denoted as P2-O3-Na 0.76 MO2) also exhibits differences in the particle surface, where surface enrichment of transition metal ions was observed by high-resolution transmission electron microscopy.

[0179] P2-O3-Na 0.76 The structure of MO2 is shown in Fig.15 (a) and Fig.15 (b) In which the P2 phase is observed in the core while the O3 phase is observed on the surface, both marked by arrows.

[0180] Fig.15 (c) shows the Fig.15 HAADF signal distribution curves for the regions marked in (b): across the cation layer in the P2 phase (1), across the cation layer in the O3 phase (2), and along the cation layer in the P2 phase (3). Arrows indicate significant HAADF signals in the interlayer space of the O3 phase. Asterisks indicate triple cycles of HAADF signals in the P2 phase along the cation layer.

[0181] Fig.15 The HAADF signal profile of c(2) shows that the O3 phase in the surface exhibits cation mixing in the sodium layer. This transition metal enrichment in the particle surface is expected to improve the material's stability to moisture by reducing surface reactivity.

[0182] Example 4

[0183] The same method as described in Example 2 was used to make the following compounds of the present invention:

[0184] P2-phase Na 0.7 Ni 0.2 Fe 0.3 Mn 0.35 Ti 0.15 O2, and

[0185] P2-phase Na 0.7 Ni 0.25 Fe 0.2 Mn 0.40 Ti 0.15 O2.

[0186] Fig.9A and Fig. 10A The X-ray diffraction patterns of the samples show that they are all in the P2 phase. Fig. 9B and Fig. 10B ) and P2 Na 0.67 Ni 0.3 Zn0.03 Mn 0.52 Ti 0.15 O2 has similar capacity, however, the amount of nickel is reduced while utilizing more of the earth-abundant Fe 3+ . Fig. 10B P2 Na 0.7 Ni 0.25 Fe 0.2 Mn 0.35 Ti 0.15 Cycling performance of O2 in a Na-ion half-cell with Na metal as the anode.

[0187] Example 5

[0188] In order to show Zn 2+ Ions are easily absorbed by other M 2+ Ions such as Cu 2+ and Mg 2+ Alternatively, the same method as described in Example 2 was used to make the following compounds of the present invention:

[0189] P2-Na 0.67 Ni 0.3 Cu 0.03 Mn 0.52 Ti 0.15 O2; and

[0190] P2-Na 0.67 Ni 0.3 Mg 0.03 Mn 0.52 Ti 0.15 O2.

[0191] Fig.11 It shows that Na 0.67 Ni 0.3 Cu 0.03 Mn 0.52 Ti 0.15 O2 and Na 0.67 Ni 0.3 Mg 0.03 Mn 0.52 Ti 0.15 The electrochemical cycle curves of O2 are similar to those of the parent phase Na 0.67 Ni 0.3 Zn 0.03 Mn 0.52 Ti 0.15 O2 is the same, in which Zn 2+ Cu 2+ or Mg 2+ replace.

[0192] Example 6

[0193] To show the importance of balancing the proper stoichiometry for controlling the final phase, the 0.76 Ni 0.35 Zn 0.03 Mn 0.52 Ti 0.1 O2 was targeted for synthesis, however excess Na2CO3 was used in the synthesis. Fig.12 XRD shows that P2-O3 Na 0.76 Ni 0.35 Zn 0.03 Mn 0.52 Ti 0.1 The formation of the O2 phase, however with excess sodium (i.e. 1.1 instead of 0.76) stabilized as a Na2CO3 second phase. By repeating the milling and reheating steps, O3Na1Ni 0.35 Zn 0.03 Mn 0.52 Ti 0.1 O2 phase, such as Fig.13 As shown, but the manganese in this material is Mn 3+ stabilized, and the material is sensitive to humid air and is unstable as an O3 phase. Fig.12 The compound was ground again and reheated to 1000°C (2 times at 1000°C for 6 hours with cooling, grinding and reheating in each step) for 6 hours. Fig.13 The obtained O3 phase shown in FIG was exposed to air for only 3 hours, reacting with moisture and producing a new phase (P3). By heating the already formed pure phase P2-O3 Na 0.76 Ni 0.35 Zn 0.03 Mn 0.52 Ti 0.1 O2 and Na2CO3 achieve the same effect.

[0194] Example 7

[0195] To show the importance of implementing slow cooling, Na was synthesized as described in Example 6 (i.e., with excess NaCO). 0.85 Ni 0.38 Zn 0.04 Mn 0.48 Ti 0.1 O2, step (c) is carried out at a temperature of 900°C for 6 hours, followed by step (e) at a temperature of 1000°C, with intermediate milling (step (d)). Step (e) is followed by slow cooling (step (f)) to a temperature of 200°C at a rate of 1°C / min.

[0196] The obtained Na 0.85 Ni 0.38 Zn0.04 Mn 0.48 Ti 0.1 The XRD pattern of O2 shows Fig.16 This indicates that a mixture of P3-O3 phases was obtained.

[0197] Fig.17 Represents P3-O3-Na 0.85 Ni 0.38 Zn 0.04 Mn 0.48 Ti 0.1 HAADF-STEM image of O2, showing the presence of surface transition metal enrichment (marked by white arrows) as well as some small particles similar to Na2CO3, which have no transition metal ions in their structure.

[0198] refer to Fig.18 It can be observed that the XRD pattern remains unchanged after exposure to humid air, indicating that P3-O3-Na 0.85 Ni 0.38 Zn 0.04 Mn 0.48 Ti 0.1 O2 is stable to humid air.

[0199] refer to Fig.19 , which shows that O3-Na 0.85 Ni 0.38 Zn 0.04 Mn 0.48 Ti 0.1 From the high temperature XRD analysis of O2, it can be observed that the initial O3 phase retains its O3 structure during heating at high temperature, and that the P3 phase begins to form during the cooling step, accompanied by the loss of sodium from the structure. In other words, the formation of the P3 phase occurs mainly during the slow cooling step of the synthesis, thus indicating the importance of the slow cooling step in forming the most thermodynamically stable structure for a given stoichiometry.

[0200] Example 8

[0201] Na was synthesized as described in Example 8 (i.e. with excess NaCO). 0.85 Ni 0.38 Zn 0.04 Mn 0.48 Ti 0.1 O2, step (c) is carried out at a temperature of 900°C for 6 h, followed by step (e) at a temperature of 1000°C, with intermediate milling (step (d)). In contrast to Example 8, in Example 9, step (e) is not followed by a slow cooling step (f), but by a cooling step (f) consisting of quenching the sample directly from 1000°C to room temperature.

[0202] As Fig. 20 As shown in (a), this synthesis produces a pure O3 phase, namely O3-Na 0.85 Ni 0.38 Zn 0.04 Mn 0.48 Ti 0.1 O2, while P3-O3-Na is obtained upon slow cooling 0.85 Ni 0.38 Zn 0.04 Mn 0.48 Ti 0.1 O2( Fig. 20 (b)).

[0203] in conclusion

[0204] All synthesized materials showed better moisture stability than the O3 materials with monosodium, with the best stability being obtained for the pure P2 phase material. 2+ 、Zn 2+ , Mn 4+ and Ti 4+ ions. In different compositions designed to obtain x = 0.67, 0.76, 0.9 and 1 (for comparison), P2 type Na 0.67 Ni 0.3 Zn 0.03 Mn 0.52 Ti 0.15 O2, the best results regarding moisture stability were achieved.

[0205] In conclusion, it is important to optimize the stoichiometry of the materials as well as the synthesis conditions to achieve the preferred electrochemical performance of the sodium layered oxides. In the formation of P2-O3 and P3-O3 structures, the slow cooling step plays a major role in stabilizing the P-type structure and forming a surface rich in transition metal layers.

[0206] When moving towards batch scale synthesis, the synthesis conditions such as calcination time, calcination temperature need to be improved since the sodium loss during the calcination step needs to be taken into account when reaching the final desired composition.

[0207] References

[0208] 1.Ivana Hasa,Sathiya Mariyappan,Damien Saurel,Philipp Adelhelm,AlexeyY.Koposov,Christian Masquelier,Laurence Croguennec,Montse Casas-Cabanas.Challenges of today for Na-based batteries of the future:Frommaterials to cell metrics.,Journal of Power Sources,482,p.228872(2020).DOI: 10.1016 / j.jpowsour.2020.228872

[0209] 2.J.-M.Tarascon,Na-ion versus Li-ion batteries:Complementary ratherthan competitive ness.Joule.4(8),p.161-1620(2020).

[0210] 3.Y.Subramanian,W.Oh,W.Choi,H.Lee,M.Jeong,R.Thanavel,W-S.Yoon,Optimizing high voltage Na3V2(PO4)2F3 cathode for achieving high rate sodiumion batteries with long cycle life.Chemical Engineering Journal.403,p.126291(2021).

[0211] 4.K.Kubota,S.Kumakura,Y.Yoda,K.Kuroki,and S.Komaba,Electrochemistryand Solid-State Chemistry of NaMeO2(Me=3d Transition Metals).Adv.EnergyMater.,8,1703415(2018).

[0212] 5.K.Smith,J.Treacher,D.Ledwoch,P.Adamson,and E.Kendrick,Novel HighEnergy Density Sodium Layered Oxide Cathode Materials:From Material toCells.ECS Trans.,75,13-24(2017).

[0213] 6.C.Delmas,C.Fouassier,and P.Hagenmuller,Structural Classificationand Properties of the Layered Oxides.Phys.BC,99,81-85(1980).

[0214] 7.M Sathiya,J Thomas,D Batuk,V Pimenta,R Gopalan,JM Tarascon,DualStabilization and Sacrificial Effect of Na2CO3 for Increasing Capacities ofNa-Ion Cells Based on P2-Na x MO2 Electrodes.Chemistry of Materials,29(14),5948-5956(2017).

Claims

1. A sodium layered oxide having formula I: <h2 style=";text-align:left;direction:ltr">Na<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> M1<h2 style=";text-align:left;direction:ltr"> a+ <h2 style=";text-align:left;direction:ltr"> 1-y-z-n <h2 style=";text-align:left;direction:ltr"> M2<h2 style=";text-align:left;direction:ltr"> b+ <h2 style=";text-align:left;direction:ltr"> y <h2 style=";text-align:left;direction:ltr"> M3<h2 style=";text-align:left;direction:ltr"> c+ <h2 style=";text-align:left;direction:ltr"> z <h2 style=";text-align:left;direction:ltr"> M4<h2 style=";text-align:left;direction:ltr"> d+ <h2 style=";text-align:left;direction:ltr"> n <h2 style=";text-align:left;direction:ltr"> O2,(I) in: M1 a+ 、M2 b+ 、M3 c+ and M4 d+ are different transition metal ions or mixtures thereof, x is a number ranging from 0.5 to less than 1; y, z, and n are numbers ranging from 0.01 to 0.85; y+z+n is less than 1; a, b, c and d are the corresponding oxidation numbers of transition metal ions M1, M2, M3 and M4, respectively; and The cumulative oxidation state of the transition metal ion a*(1-yzn)+(b*y)+(c*z)+(d*n) is equal to 4-x; And wherein the sodium layered oxide having formula I is not P2-Na 2 / 3 Ni 1 / 4 Mn 1 / 2 Ti 1 / 6 Zn 1 / 12 O2 or P2-Na 2 / 3Ni 1 / 4 Mn 1 / 2 Ti 1 / 6 Mg 1 / 12 O2.

2. The sodium layered oxide according to claim 1, wherein The crystal structure of the sodium layered oxide is selected from the group consisting of: O3 when x ranges from 0.8 to less than 1; P2-O3 mixture when x ranges from 0.7 to 0.8; P3-O3 mixture when x ranges from 0.7 to 0.85; and P2 when x≤0.7; preferably, the crystal structure of the sodium layered oxide is a P2-O3 or P3-O3 structure.

3. The sodium layered oxide according to claim 1 or 2, wherein M1 is Ni.

4. The sodium layered oxide according to any one of claims 1 to 3, wherein M2, M3 and M4 are selected from the group consisting of: Mg, Zn, Cu, Fe, V, Cr, Mn, Ge, Sn, Ti, Zr, Co and mixtures thereof, preferably from the group consisting of: Zn, Mn, Ti, Cu, Fe, Mg and mixtures thereof, and even more preferably from the group consisting of: Zn, Mn and Ti.

5. The sodium layered oxide according to claim 4, wherein M1, M2, M3 and M4 are Ni, Zn, Mn and Ti respectively.

6. The sodium layered oxide according to any one of claims 1 to 3, wherein M1 is Ni, M2 and M4 are Mn or Ti, and y is less than 0.07, advantageously less than 0.06 and preferably less than 0.

05.

7. The sodium layered oxide according to any one of claims 1 to 4, having the formula Na 0.67 Ni 0.3 Zn 0.03 Mn 0.52 Ti 0.15 O2、Na 0.76 Ni 0.35 Zn 0.03 Mn 0.52 Ti 0.1 O2、Na 0.85 Ni 0.38 Zn 0.04 Mn 0.48 Ti 0.1 O2、Na 0.9 Ni 0.45 Zn 0.05 Mn 0.4 Ti 0.1 O2、Na 0.7 Ni 0.2 Fe 0.3 Mn 0.35 Ti 0.15 O2、Na 0.7 Ni 0.25 Fe 0.2 Mn 0.40 Ti 0.15 O2、Na 0.67 Ni 0.3 Cu 0.03 Mn 0.52 Ti 0.15 O2 or Na 0.67 Ni 0.3 Mg 0.03 Mn 0.52 Ti 0.15 O2.

8. The sodium layered oxide according to claim 7, wherein the sodium layered oxide has the formula Na 0.67 Ni 0.3 Zn 0.03 Mn 0.52 Ti 0.15 O2、Na 0.76 Ni 0.35 Zn 0.03 Mn 0.52 Ti 0.1 O2 or Na 0.85 Ni 0.38 Zn 0.04 Mn 0.48 Ti 0.1 O2, advantageously P2-Na 0.67 Ni 0.3 Zn 0.03 Mn 0.52 Ti 0.15 O2, P2-O3-Na 0.76 Ni 0.35 Zn 0.03 Mn 0.52 Ti 0.1 O2 or P3-O3-Na 0.85 Ni 0.38 Zn 0.04 Mn 0.48 Ti 0.1 O2.

9. A method for preparing a sodium layered oxide having formula I according to any one of claims 1 to 8: The method comprises the following steps: (a) mixing a powder of a sodium precursor and a transition metal precursor of the sodium layered oxide in stoichiometric amounts to obtain a solid powdery mixture; (b) heating the solid powdery mixture in an air atmosphere at a temperature ranging from 500° C. to 900° C. to obtain a calcined powder; (c) cooling the calcined powder at a rate of 1.5° C. / min or less; (d) grinding the calcined powder to obtain a ground calcined powder; (e) heating the solid powdery mixture in an air atmosphere at a temperature ranging from 700° C. to 1100° C. to obtain a ground re-calcined powder; and (f) cooling the re-calcined powder, advantageously at a rate of 1.5° C. / min or less.

10. An electrode material comprising: - The sodium layered oxide according to any one of claims 1 to 8; - conductive additives, such as carbon black; and -Optionally a polymeric binder.

11. An electrochemical cell comprising: - electrolytes; - a negative electrode configured to reversibly accept sodium ions from an electrolyte and reversibly release sodium ions into the electrolyte, the negative electrode having at least one current collector; - a positive electrode comprising the sodium layered oxide according to any one of claims 1 to 8 or the electrode material according to claim 10, the positive electrode being configured to reversibly accept sodium ions from the electrolyte and reversibly release sodium ions into the electrolyte, the positive electrode having at least one current collector; and - a separator admixed with said electrolyte comprising sodium ions, said separator being in contact with both said negative electrode and said positive electrode.

12. The electrochemical cell according to claim 11, wherein: The separator is selected from the group consisting of glass fiber, polyolefin separator and cellulose based membrane.

13. The electrochemical cell according to claim 11 or 12, wherein: The negative electrode comprises sodium metal, a carbonaceous compound, hard carbon, antimony, tin, phosphorus or a mixture thereof.

14. The electrochemical cell according to any one of claims 11 to 13, wherein: The battery cell is a button battery cell, a pouch battery cell, a cylindrical battery cell, or a prismatic battery cell.

15. The electrochemical cell according to any one of claims 11 to 14, wherein: The electrolyte comprises: - sodium salts, such as NaPF6, NaClO4, NaFSI, NaTFSI, NaBETI, NaBF4, Na[B(hexafluoroisopropoxy, OiPrF)4], Na[B(perfluoropinacol, O2C2(CF3)4)2] or mixtures thereof; - solvents such as dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, propylene carbonate, ethylene carbonate; esters such as methyl acetate, ethyl acetate, ethyl propionate, or methyl propionate, or mixtures thereof; and - Optionally, additives such as vinylene carbonate, 1,3-propane sultone, succinonitrile, sodium difluoro(oxalato)borate or mixtures thereof.

16. A battery comprising a series of electrochemical cells according to any one of claims 11 to 15.

17. Use of the sodium layered oxide according to any one of claims 1 to 8 as electroactive compound in a battery cell or battery, preferably as positive electrode material.

Citation Information

Patent Citations

  • Active cathode material and its use in rechargeable electrochemical cells

    EP3121879A1

  • Layered active material for na-ion batteries

    WO2020260294A1

Cited By

  • Positive electrode material, sodium ion battery and electric equipment

    CN115602814A

  • Positive electrode material, sodium-ion battery and electric device

    CN115602814B